Comprehensive review on efficacy and safety evaluation of laxatives of traditional medicinal plants of India: EVALUATION OF HERBALS LAXATIVES MENTIONED IN AYURVEDA (Indian Journal of Traditional Knowledge (IJTK), 2026)
Ayurveda, uses a holistic approach to cure any disorder, among which constipation is one entity. The entity, such as constipation or any gut disorder associated with the constipated bowel, should be treated with laxatives. Herbal laxatives are considered the best option, as they have the least prolonged or unwanted complications. Ayurveda houses multiple drugs that are indicated specifically as needed. This study aims to group drugs derived under one umbrella from different classes, such as Charaka, Sushruta and Bhav Prakash, and is supported by scientific evidence from in vivo studies or clinical trials available from various resources. Herbal laxatives have a defined potential clinically but need more scientific evidence for validation and to be set as standards.